Self-motion and heterogeneous droplet dynamics in moderately attractive dense emulsions. (21st April 2021) - Kim, Ha Seong; Xu, Yixuan; Scheffold, Frank; Mason, Thomas G
Abstract: We show that diffusing wave spectroscopy (DWS) is sensitive to the presence of a moderate short-range attraction between droplets in uniform fractionated colloidal emulsions near and below the jamming point associated with monodisperse hard spheres. This moderate interdroplet attraction, induced by micellar depletion, has an energy of about ∼2.4 k B T, only somewhat larger than thermal energy. Although changes in the mean free path of optical transport caused by this moderate depletion attraction are small, DWS clearly reveals an additional secondary decay-to-plateau in the intensity autocorrelation function at long times that is not present when droplet interactions are nearly hard. We hypothesize that this secondary decay-to-plateau does not reflect the average self-motion of individual droplets experiencing Brownian excitations, but instead results from heterogeneous dynamics involving a sub-population of droplets that still experience bound motion yet with significantly larger displacements than the average. By effectively removing the contribution of this secondary decay-to-plateau, which is linked to greater local heterogeneity in droplet structure caused by the moderate attraction, we obtain self-motion mean square displacements (MSDs) of droplets that reflect only the initial primary decay-to-plateau. Moreover, we show that droplet self-motion primary plateau MSDs can be interpreted using the generalized Stokes-Einstein relation of passive microrheology, yielding quantitative agreement with plateau elastic shear moduli measured mechanically.